2019
DOI: 10.1103/physrevapplied.11.064013
|View full text |Cite
|
Sign up to set email alerts
|

Single-Laser Krypton Tagging Velocimetry Investigation of Supersonic Air and N2 Boundary-Layer Flows over a Hollow Cylinder in a Shock Tube

Abstract: In this paper, we investigate the boundary-layer profiles that form over a sharp, hollow cylinder in supersonic air and N 2 flows with a krypton tagging velocimetry (KTV) single-laser scheme. The supersonic flows are generated by the passage of the primary shock wave over the model in the Stevens shock tube. The experiments are performed in two gas mixtures doped with Kr: 99% N 2 /1% Kr, to model N 2 , and 75% N 2 /20% O 2 /5% Kr, to model air. The experimental setup allows us to vary the pressure and Reynolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…We found these levels of Kr doping to be sufficient in previous experiments (Mustafa et al. 2019b ). Referring to the energy level diagram in Fig.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…We found these levels of Kr doping to be sufficient in previous experiments (Mustafa et al. 2019b ). Referring to the energy level diagram in Fig.…”
Section: Discussionsupporting
confidence: 72%
“…The experimental conditions in Mustafa et al. ( 2019b ) showed that KTV could be performed at static conditions similar to the T5 freestream with 99% N /1% Kr, and 75% N /20% O /5% Kr gas mixtures. Relative to Mustafa et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations